Screening of ESBL (Extended Spectrum of Î² - Lactamases) and Amp C Î² - Lactamases Producers among Pathogens Causing Urinary Tract Infections - R, Suresh kumar. (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTESBL (Extended Spectrum of Î²- Lactamase) continue to be major problem in clinical world and exhibit co-resistance to many other classes of antibiotic resulting in limitation of therapeutic option. The purpose of the study was to simultaneously screen for ESBL and Amp-C Î²- lactamase in Gram negative isolates from hospital. It is a plasmid mediated enzymes first isolated in Europe in 1980, most commonly found in Klebsiella followed by Escherichia coli. These enzymes are capable of hydrolysing broad spectrum Cephalosporins and Monobactams, but inactive against Cephamycins and Imipenem. ESBL have serine at their active site and attack amide bond in the Î² lactam ring of antibiotic causing their hydrolysis. A total of 60 clinical isolates comprising Escherichia coli (n=44,73), Klebsiella sp. (n=10,17), Proteus sp. (n=3) and Pseudomonas sp. (n=3) were recovered from urine sample over a period of four months (January to April 11). Antibiogram profiles of these isolates were determined along with screening for ESBL and Amp-C Î²- lactamase production by phenotypic detection method as recommended by the Clinical Labarotory Standard Institute (CLSI). Two tests were performed for each, combination disk and synergy for ESBL and three dimensional and disk antagonism test for Amp-C Î²- lactamase detection. Out of the 60 isolates, 42 (70%) isolates were found to be ESBL producer. From these, 34 (81%) Escherichia coli, 6 (14%) Klebsiella sp., 2 (5%) Proteus sp. Amp-C was found to be 20 (43%) isolates, of these 17 (85%) Escherichia coli and 3 (15%) Pseudomonas sp. Then, the Prevalence of ESBL producer was found to be 70% (42/60). All the isolates were sensitive to Imipenem.